2021
DOI: 10.1007/s00431-021-04219-4
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of immunization status in patients with cerebral palsy: a multicenter CP-VACC study

Abstract: Children with chronic neurological diseases,including cerebral palsy(CP)are especially susceptible to vaccine-preventable infections and face an increased risk of severe respiratory infections and decompensation of their disease.This study aims to examine age-appropriate immunization status and related factors in the CP population of our country. This cross-sectional prospective multicentered survey study included 18 pediatric neurology clinics around Turkey,wherein outpatients children with CP were included i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
(20 reference statements)
0
3
0
Order By: Relevance
“…Our study also showed that the age at diagnosis of CP was ≤ 3 years in all children and all were fully vaccinated. A recent study from Turkey suggested that the frequency of incomplete/no routine immunizations, except pneumococcal immunization, is higher in patients with severe motor dysfunction than in CP children with mild to moderate motor dysfunction ( CP ) (7). In our study, all children at each level of the Gross Motor Function Classification System (GMFCS) were fully vaccinated, possibly because there were no contraindications to vaccines and no history of serious adverse events after immunization in the participants in this study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our study also showed that the age at diagnosis of CP was ≤ 3 years in all children and all were fully vaccinated. A recent study from Turkey suggested that the frequency of incomplete/no routine immunizations, except pneumococcal immunization, is higher in patients with severe motor dysfunction than in CP children with mild to moderate motor dysfunction ( CP ) (7). In our study, all children at each level of the Gross Motor Function Classification System (GMFCS) were fully vaccinated, possibly because there were no contraindications to vaccines and no history of serious adverse events after immunization in the participants in this study.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, parents were not adequately informed by healthcare professionals about optional childhood vaccines, and none of the children with CP received the full series of optional childhood vaccines. In Turkey, the influenza vaccine was never recommended for 93.9% of children with CP (7). The percentage of Turkish family physicians and pediatricians who recommend the meningococcal conjugate vaccine to their patients was given as 57.5% and 71.2%, respectively (24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation